2016
DOI: 10.1111/jomf.12386
|View full text |Cite
|
Sign up to set email alerts
|

Children's Experiences of Time When a Parent Travels for Work

Abstract: This qualitative study focuses on different ways time is experienced by children in families who face time challenges due to a family member’s job that required work travel. Data are from a family-level study that includes interviews of all family members over the age of 7. Using grounded theory methodology, this study illustrates ways in which job demands and family processes interact. Analysis centers on the 75 children’s perspectives from 43 families. Holding together assessments of having enough time while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 63 publications
(83 reference statements)
0
7
0
Order By: Relevance
“…In another vein, few studies examine children's assessment of parental work, even though earlier work suggested that these perceptions are consequential for children's well‐being (Galinksy, ). Zvonkovic, Swenson, and Cornwell () found that children had gendered interpretations of their parents' job involvement, calling mothers “rushed” and distracted, but calling fathers “chill” (see also Strazdins, Baxter, & Li, ). In a rare qualitative study examining fathers' engagement with their college‐aged sons across race, Ide, Harrington, Wiggins, Whitworth, and Gerstel () found that when compared with White and African American sons, Asian American sons were more likely to disparage their fathers for what they perceived as their overinvolvement in breadwinning, which detracted from their engagement in family life (Chung, ; but see also Park [], who found that Asian sons and daughters at elite schools valued their father's career engagement as it provided resources for children's careers).…”
Section: Unpaid Work and Familiesmentioning
confidence: 99%
“…In another vein, few studies examine children's assessment of parental work, even though earlier work suggested that these perceptions are consequential for children's well‐being (Galinksy, ). Zvonkovic, Swenson, and Cornwell () found that children had gendered interpretations of their parents' job involvement, calling mothers “rushed” and distracted, but calling fathers “chill” (see also Strazdins, Baxter, & Li, ). In a rare qualitative study examining fathers' engagement with their college‐aged sons across race, Ide, Harrington, Wiggins, Whitworth, and Gerstel () found that when compared with White and African American sons, Asian American sons were more likely to disparage their fathers for what they perceived as their overinvolvement in breadwinning, which detracted from their engagement in family life (Chung, ; but see also Park [], who found that Asian sons and daughters at elite schools valued their father's career engagement as it provided resources for children's careers).…”
Section: Unpaid Work and Familiesmentioning
confidence: 99%
“…The question of how and under which conditions parents' early and current employment affects the lives of their children is an area ripe for development. In addition, understanding the ways in which children experience their parents' work is an area ripe for inquiry (Zvonkovic, Swenson, & Cornwell, ). Both ecological and life course frames highlight the value of considering how social contexts, defined by social class, race, ethnicity, gender, and family structure, moderate work socialization processes.…”
Section: The 21st Centurymentioning
confidence: 99%
“…Work travel is a highly variable experience (especially after the Great Recession beginning in 2007), with travellers often having to adjust to travelling with short notice, cancellations, and little control over their work trips (Swenson & Zvonkovic, 2016). Work travel, as it requires workers to be distant from their families and away for extended periods, may affect the worker and members of the family (Swenson, Zvonkovic, Rojas-McWhinney, & Gerst, 2015; Zvonkovic, Swenson, & Cornwell, 2016). Prior literature has not yet established a consensus of a threshold above which work travel affects individuals or families, but it can be concluded that examining the frequency of being away from home would be important (Casinowsky, 2013; Espino, Sundstrom, Frick, Jacobs, & Peters, 2002; Westman et al, 2009).…”
Section: Parental Work Travelmentioning
confidence: 99%
“…Particular arrangements and rearrangements of family roles may occur as families cope with the entry and departure of the family member who travels. There is some evidence that children may have a difficult time distinguishing the time parents are travelling from long work hours (Zvonkovic et al, 2016). Little research has examined how these arrangements and schedule disruptions because of work travel (instead of just long work hours) influence families, especially the relationships between parents and children.…”
Section: Parental Work Travelmentioning
confidence: 99%
See 1 more Smart Citation